Land use intensification and implications on land degradation in the Boteti area: Botswana. Issue 1 (2nd January 2019) - Sebego, R.J.; Atlhopheng, J.R.; Chanda, R.; Mulale, K.; Mphinyane, W.
Abstract: Arid and semi-arid areas worldwide face challenges of over utilization of rangelands, with a possibility of declining into degraded lands. Overgrazing by livestock and persistent deforestation of woodlands has been reported in the rangelands of Boteti Sub- District of Botswana. This study focuses on depicting changing patterns of land use that have come about as a result of a forcing from natural phenomenon. Periodic droughts and the drying up of the Boteti river which has been a source of livelihood for a long time has manifested on land utilization trends around the villages of Boteti District. New patterns of land use have since emerged as an adaptation strategy against the drier environment. The study mapped land use and land cover around two 'river village settlements'. Land degradation indicators were identified within the various land cover categories. Results show that communities have shifted from flood recession farming to dry-land farming with emphasis on livestock. The latter are ironically privileged by government policies that are skewed toward livestock production, especially the introduction of fenced private ranches and conservation areas. As a result, they have relentlessly exerted more pressure on the communal land, manifesting itself through moderate to severe incidents of land degradation.